Comparison of intralesional verapamil versus intralesional corticosteroids in treatment of keloids and hypertrophic scars: A randomized controlled trial. Issue 6 (September 2018) - Abedini, Robabeh; Sasani, Pardis; Mahmoudi, Hamid Reza; Nasimi, Maryam; Teymourpour, Amir; Shadlou, Zahra
Highlights: Mean zero VSS scores were achieved with only triamcinolone in respect of scar height (week 15th) and pliability (week 15th). No significant improvement were seen in verapamil group. Our results did not support verapamil in treatment of keloid nor hypertrophic scars. Abstract: Background: Keloids and hypertrophic scars are due to overgrowth of dermal collagen following trauma to the skin that usually cause major physical, psychological and cosmetic problems. Methods: In this randomized controlled trial, with a paired design, 50 patients with 2 or more keloids were included. In the control group (50 lesions), intralesional triamcinolone acetonide (40 mg/mL) was injected at three-week intervals for a total of 18 weeks. In the other group (50 lesions), lesions were treated by verapamil (2.5 mg/mL) with the same therapeutic sessions. Scar evaluation at each stage and at the end of 3 months follow up was done by serial photographic records as well as by Vancouver Scar Scale (VSS). Results: Mean zero VSS scores were achieved with only triamcinolone in respect of scar height (week 15th) and pliability (week 15th). No therapeutic event (parameter = 0) or significant improvement was seen in verapamil group. Conclusion: Our results did not support verapamil's capability in treatment of keloid nor hypertrophic scars.